SIMULATION OF BIO-MECHATRONIC ELECTRICAL SUBSTATION USING RENEWABLE ENERGY - Bulgakov, Alexey Grigoryevich; Sayfeddine, Daher (Journal of Applied Engineering Science, 2017)
More attention is being offered to renewable energy due to its cost effectiveness, ecological compatibility and optimized service transportation. In fact, many governments are dictating green energy standards to newly constructed buildings and compounds. Realizing its importance and ability to replace traditional energy sources, the green energy resources requires infrastructures and setups thus to generate consistent and reliable power. In view of that, the paper studies a bio-mechatronic control and monitoring system for an electrical substation using the internal wave energy. The electrical substation is part of self-sufficient standalone agro-industrial compound. The paper is structured around adequate mathematical model of the bio-mechatronic electrical substation and supported by simulation results of generating consistent electrical power and Steady–state stator current.
Keywords: Renewable energy; Bio-mechatronic system; Green energy